Suicidal Deaths Amid COVID-19 Pandemic: A Cross-Sectional Autopsy-Based Study - Tanmay Sardar; Ranjan Biswas; Achintya Biswas; Saptarshi Chatterjee (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Suicide is a global issue, with an estimated 75.5% of the cases occurring in developingcountries, and India alone accounting for 26.6% of all global suicidal deaths. With an advent of COVID-19in the early months of 2020, India observed a rapid rise in suicidal deaths. Though, various media reportspredicted loneliness, mental illness and economical instabilities as the major triggering factors, there isa lack of analytical or descriptive studies confirming this hypothesis. In this context, the present crosssectionalstudy was planned to determine the socio-demographic profiles of the victims and the triggeringfactors of the suicidal deaths during the COVID-19 phase, in context to the victims of suicide from 2017 tothe Pre-COVID phase.Methods: The present cross-sectional study was conducted by analyzing the suicidal deaths from 2017 to30th June, 2020, interviewing the deceased family members during the COVID-19 phase and studying theInquest reports, with the documents from the Institutional Medical Record Section.Conclusion: The authors feel that suicide is an act of moment in mind, so any decision made under excitementor incitement is the real culprit. To curb the menace of suicide, state and society should ensure education,employment and socioeconomic well-being, along with strict law enforcement.